2014
DOI: 10.3389/fnhum.2014.00362
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the where and when of tic generation and resting state networks in adult Tourette patients

Abstract: Introduction: Tourette syndrome (TS) is a neuropsychiatric disorder with the core phenomenon of tics, whose origin and temporal pattern are unclear. We investigated the When and Where of tic generation and resting state networks (RSNs) via functional magnetic resonance imaging (fMRI).Methods: Tic-related activity and the underlying RSNs in adult TS were studied within one fMRI session. Participants were instructed to lie in the scanner and to let tics occur freely. Tic onset times, as determined by video-obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
139
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 88 publications
11
139
1
8
Order By: Relevance
“…Two seconds before tic: activation of supplementary motor area, ventral primary motor cortex, primary sensorimotor cortex, parietal operculum, 12 fMRI fMRI uses task-based changes in blood flow measured by blood-oxygen-level-dependent contrast in order to examine neural activity in the brain.…”
Section: Petmentioning
confidence: 99%
See 2 more Smart Citations
“…Two seconds before tic: activation of supplementary motor area, ventral primary motor cortex, primary sensorimotor cortex, parietal operculum, 12 fMRI fMRI uses task-based changes in blood flow measured by blood-oxygen-level-dependent contrast in order to examine neural activity in the brain.…”
Section: Petmentioning
confidence: 99%
“…11,12 The temporal pattern of tic generation was found to follow the cortico-striato-thalamo-cortical circuit. 12 Several studies found activation in the supplementary motor area (SMA), ventral primary motor cortex, primary sensorimotor cortex, the parietal operculum, 12,13 and anterior cingulate cortex 13 2 s before tic onset. One second before a tic, the anterior cingulate cortex, putamen, insula, amygdala, cerebellum, and the extrastriatal-visual cortex showed activation.…”
Section: Tics Premonitory Urges and Tic Suppression Ticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuner et al 13 examined tic-related neural activity in ten adults with TS using fMRI, estimating the timing of brain activity (as reflected by BOLD signal) to a resolution shorter than that of the individual image acquisitions by taking advantage of the essentially random temporal distribution of tics with respect to the timing of image acquisition. This strategy is reminiscent of the event-related analysis of positron emission tomography regional brain blood flow images developed by Silbersweig and colleagues 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Five basal ganglia loops have been outlined [3], which when dysfunctional, have motor and/or cognitive implications, with the sensory-motor loop (sensory-motor and supplementary motor cortex; dorsolateral putamen; ventrolateral globus pallidus and ventrolateral thalamus) primarily being affected in TS [4]. Functional structural and diffusion magnetic resonance imaging (MRI) have also pointed to immature and anomalous patterns of functional and structural connectivity in resting state networks such as the default mode network [5,6]. Resting-state functional connectivity MRI has implicated deviation of connectivity in the fronto-parietal network, important for online adaptive control [7,8].…”
mentioning
confidence: 99%